2011
DOI: 10.1016/j.iatssr.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating CO2 emissions, cost, and service quality trade-offs in an urban delivery system case study

Abstract: a b s t r a c tGrowing pressure to limit greenhouse gas emissions is changing the way businesses operate. This paper presents the trade-offs between cost, service quality (represented by time window guarantees), and emissions of an urban pickup and delivery system under these changing pressures. A model, developed by the authors in ArcGIS, is used to evaluate these trade-offs for a specific case study involving a real fleet with specific operational characteristics. The problem is modeled as an emissions minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Moreover, the research described in this paper could be extended by considering emissions produced by light and heavy goods' vehicles, in consideration of the growing importance of environmental aspects in the context of urban freight delivery systems [45,46]. Finally, with specific reference to the roundabout, it would be interesting to assess the impact on emissions of conflicting pedestrian flows on intersection crosswalks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the research described in this paper could be extended by considering emissions produced by light and heavy goods' vehicles, in consideration of the growing importance of environmental aspects in the context of urban freight delivery systems [45,46]. Finally, with specific reference to the roundabout, it would be interesting to assess the impact on emissions of conflicting pedestrian flows on intersection crosswalks.…”
Section: Discussionmentioning
confidence: 99%
“…However where these can be mutually supportive; there are opportunities to reduce the carbon intensity of the freight industry. It has previously been reported that CO₂ and cost "trend together" and therefore increasing the cost of fuel is an effective approach to encourage freight companies and drivers to limit their emissions (Wygonik & Goodchild, 2011). Transitioning away from road transport for urban freight deliveries seems unlikely, yet for national delivery, rail could provide a low-carbon option, but the current climate for time sensitive deliveries, along with a lack of political support for rail, might hamper the reintroduction of freight as a major national freight delivery mode in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…The first scenario explored is inspired by the work of Wygonik [32]. A personal vehicle travel scenario is defined as a scenario where a combination truck delivers goods from a regional warehouse to local depots while customers use personal vehicles to drive from their homes to pickup goods from local depots.…”
Section: Personal Vehicle Travel Scenariomentioning
confidence: 99%